Biogeographical and bioclimatic outline of Antarctica. (5th November 2020) - Rivas-Martínez, Salvador; del Río, Sara; Penas, Ángel; Herrero, Luis; Prieto, Ignacio; Álvarez, Miguel; Díaz, Tomás E.; Molero, Joaquín; Rivas-Sáenz, Salvador; Cantó, Paloma; Costa, Manuel; Sancho, Leopoldo G.
Abstract: This study proposes a bioclimatic characterization and a new biogeographic division for the Antarctic territories up to the province level following the criteria and models of Rivas-Martínez et al. The Antarctic Kingdom comprises the continent of Antarctica, the surrounding ice-covered Antarctic islands, and the associated cold oceanic islands and archipelagos. It has two biogeographic regions: the Antarctic Region and the Subantarctic Insular Region. The Antarctic Region includes the entire pergelid Antarctic continent and the surrounding islands and archipelagos, and is characterized by upper suprapolar hyperoceanic and oceanic or Polar pergelid bioclimates on the coasts. The region has been divided into three pr6ovinces: Maritime Antarctica, West Antarctica and East Antarctica. The Subantarctic Insular Region comprises the circumantarctic islands and archipelagos that are widespread at the southern tip of the planet's most important oceans, mostly in the subtemperate latitudinal zone inside or not far from the Antarctic Convergence. Bioclimatically, all insular subantarctic territories (excluding the South-American Tierra de Fuego, Terra Magellanica and large islands) are characterized by thermo-suprapolar and semipolar antarctic hyperoceanic bioclimates on the coasts. Four provinces – Falklandian-South Georgian, Kerguelenian, Macquarian and Aucklandian-Campbellian – have been recognized in this region. All these units are characterized by floristic bioindicators.